Identification of potent tricyclic prodrug S1P1 receptor modulators12. Issue 4 (1st December 2016) - Marcoux, David; Xiao, Hai-Yun; Murali Dhar, T. G.; Xie, Jenny; Lehman-McKeeman, Lois D.; Wu, Dauh-Rurng; Dabros, Marta; Yang, Xiaoxia; Taylor, Tracy L.; Zhou, Xia D.; Heimrich, Elizabeth M.; Thomas, Rochelle; et al.
Abstract : Herein, S1P1 partial agonists with shorter half-life than our previous clinical candidate are reported. The pulmonary and cardiac safety are assessed, issues currently observed with commercial Gilenya. Abstract : Recently, our research group reported the identification of prodrug amino-alcohol2 as a potent and efficacious S1P1 receptor modulator. This molecule is differentiated preclinically over the marketed drug fingolimod (Gilenya1 ), whose active phosphate metabolite is an S1P1 full agonist, in terms of pulmonary and cardiovascular safety. S1P1 partial agonist2, however, has a long half-life in rodents and was projected to have a long half-life in humans. The purpose of this communication is to disclose highly potent partial agonists of S1P1 with shorter half-lives relative to the clinical compound2 . PK/PD relationships as well as their preclinical pulmonary and cardiovascular safety assessment are discussed.